Pulmonary artery catheter use in acute myocardial infarction‐cardiogenic shock - Saraschandra Vallabhajosyula; Aditi Shankar; Sri Harsha Patlolla; Abhiram Prasad; Malcolm R. Bell; Jacob C. Jentzer; Shilpkumar Arora; Saarwaani Vallabhajosyula; Bernard J. Gersh; Allan S. Jaffe; David R. Holmes Jr; Shannon M. Dunlay; et al. (ESC Heart Failure)
Abstract Aims The aim of this study is to evaluate the contemporary use of a pulmonary artery catheter (PAC) in acute myocardial infarction‐cardiogenic shock (AMI‐CS). Methods and results A retrospective cohort of AMI‐CS admissions using the National Inpatient Sample (2000–2014) was identified. Admissions with concomitant cardiac surgery or non‐AMI aetiology for cardiogenic shock were excluded. The outcomes of interest were in‐hospital mortality, resource utilization, and temporal trends in cohorts with and without PAC use. In the non‐PAC cohort, the use and outcomes of right heart catheterization was evaluated. Multivariable regression and propensity matching was used to adjust for confounding. During 2000–2014, 364 001 admissions with AMI‐CS were included. PAC was used in 8.1% with a 75% decrease during over the study period (13.9% to 5.4%). Greater proportion of admissions to urban teaching hospitals received PACs (9.5%) compared with urban non‐teaching (7.1%) and rural hospitals (5.4%); P < 0.001. Younger age, male sex, white race, higher comorbidity, noncardiac organ failure, use of mechanical circulatory support, and noncardiac support were independent predictors of PAC use. The PAC cohort had higher in‐hospital mortality (adjusted odds ratio 1.07 [95% confidence interval 1.04–1.10]), longer length of stay (10.9 ± 10.9 vs. 8.2 ± 9.3 days), higher hospitalization costs ($128 247 ± 138 181 vs. $96 509 ± 116 060), and lesser discharges to home (36.3% vs. 46.4%) (all P < 0.001). In 6200 propensity‐matched pairs, in‐hospital mortality was comparable between the two cohorts (odds ratio 1.01 [95% confidence interval 0.94–1.08]). Right heart catheterization was used in 12.5% of non‐PAC admissions and was a marker of greater severity but did not indicate worse outcomes. Conclusions In AMI‐CS, there was a 75% decrease in PAC use between 2000 and 2014. Admissions receiving a PAC were a higher risk cohort with worse clinical outcomes.